Analisis Akurasi dan Presisi Sensor Ultrasonik Estimasi Level Tong Sampah Pintar Berbasis Arduino - Violla Gunova (Asosiasi Dosen Muda Indonesia, 2026)
This study analyzes the accuracy and precision of ultrasonic sensors for estimating waste levels in two sizes of Arduino-based smart trash cans in a community service program at a private high school in Jambi City. Two cardboard trash can prototypes were used as learning media, namely a small trash can measuring 10 cm × 10 cm × 20 cm and a large trash can measuring 30 cm × 30 cm × 50 cm. The testing was conducted by measuring the distance between the sensor and the surface of the waste/object at several predetermined reference distances using a ruler. For each distance condition, 10 readings were taken at 2-second intervals. The evaluation parameters included the mean, standard deviation (SD), bias, MAE, and RMSE. The results show that the average readings on both prototypes were close to the reference distance with a small bias. The variation in readings tended to increase at close distances, with the highest SD at a distance of 5 cm for both bins. When the bins were empty (20 cm for the small bin and 50 cm for the large bin), the measurements tended to be more accurate and precise than when the bins were full. In aggregate, the MAE and RMSE of the large bin (≈0.166 cm and ≈0.235 cm) were smaller than those of the small bin (≈0.225 cm and ≈0.335 cm). These findings confirm that ultrasonic sensors are suitable for monitoring waste levels, with the recommendation to avoid readings at very close distances and to apply data processing to improve the stability of level estimates.